PEMANFAATAN REPRESENTASI DALAM MENYELESAIKAN PERMASALAHAN PADA MATERI SPLDV - Vania Bertha Amanda; Indaryanti Indaryanti (IKIP Siliwangi, 2023)
This study aims to look at and describe students' representation abilities in the matter of a system of two-variable linear equations (SPLDV) after the application of the Problem Based Learning (PBL) model. The research method used was descriptive with quantitative and qualitative data analysis according to the indicators of mathematical representation. This research was conducted at SMPN 6 Indralaya Utara in class VIII 1 involving 28 students as subjects. Data collection was carried out by giving tests in the form of description questions and the results of interviews with students. The collected data was subsequently examined using scoring criteria that make reference to indicators of mathematical representation. After that, the outcome of the data analysis was divided into three groups: high, medium, and low. Based on the results of data analysis, it was found that students' mathematical representation abilities in the matter of a two-variable linear equation system after the implementation of the PBL model were in the medium category with an average score of 51.12 and an average score for the symbolic representation indicator that was 75, visual representation 48 .21 and verbal 33.04.